Reducing the risk of developing walled‐off necrosis in patients with acute necrotic collection using recombinant human soluble thrombomodulin. (14th July 2021) - Eguchi, Takaaki; Tsuji, Yoshihisa; Okada, Akihiko; Inoue, Dai; Tokumasu, Hironobu; Iwane, Kosuke; Nakai, Yoshitaka; Kusaka, Toshihiro; Uenoyama, Yoshito; Fujita, Koichi; Yokode, Masataka; Yamashita, Yukimasa; et al.
Abstract: Background/Purpose: The purpose of the present study was to investigate the possibility of reducing clinical impacts of acute necrotic collection (ANC) on patients with acute pancreatitis (AP) using recombinant human soluble thrombomodulin (rTM). Methods: In this retrospective multicenter study, 233 consecutive AP patients with ANC and acute peripancreatic fluid collection (APFC) from 2012 to 2016 were enrolled. To assess clinical impacts of ANC, severity on admission (JPN score, JPN CT grade, and Modified CT severity index), development of walled‐off necrosis (WON), imaging costs for follow‐up, and mortality were recorded. Finally, we investigated whether rTM could reduce the clinical impacts, adjusting the severity using propensity analysis with Inverse probability of treatment weighting. Results: Patients with ANC developed WON with higher ratio than APFC (58/98 [59.2%] vs 20/135 [14.8%], OR = 8.3, P  < .01]. Severity on admission and imaging costs for follow‐up in ANC patients were significantly higher than those in APFC ( P  < .01). However, regarding mortality, there was no significant difference between patients with ANC and APFC ( P  = .41). Adjusting severity, it was revealed that rTM administration significantly reduced the risk of ANC developed WON (OR = 0.23, P  = .01). Conclusions: While ANC had a higher clinical impact than that of APFC, we found that early administration of rTM may reduce the impact. Abstract : Highlight In this retrospective multicenter study, Eguchi and colleagues revealed that the risk of walled‐of necrosis was higher in patients with acute necrotic collection than in those with acute pancreatic fluid collection. The risk was associated with higher imaging costs. Adjusting severity, recombinant human soluble thrombomodulin administration significantly reduced the risk.